School of English in Journalism - O. K. Ilyina (Vestnik MGIMO-Universiteta)
Department of English Language № 3 was established in 1976 and leads the teaching of English language at the Faculty of International Journalism. The Department trains future international journalists, PR-professionals as well as experts in the field of sociology of mass communications. Since early 2010 the department has been headed by Olga K. Ilyina, PhD in Philology, Associate Professor. Since the opening of the specialty "Public Relations" at the Faculty of International Journalism the Department staff has done a great job providing educational materials for the teaching process, which include textbooks and manuals that contribute significantly to the education of highly qualified specialists. Since the early1990s in the department has created 32 textbooks and teaching materials.